Expectation Damages, Divisible Contracts, and Bilateral Investment - Ohlendorf, Susanne (American Economic Review, 2009)
This paper examines the efficiency of expectation damages as a breach remedy in a bilateral trade setting with renegotiation and relationship-specific investment by the buyer and the seller. As demonstrated by Edlin and Reichelstein (1996), no contract that specifies only a fixed quantity and a fixed per-unit price can induce efficient investment if marginal cost is constant and deterministic. We show that this result does not extend to more general payoff functions. If both parties face the risk of breaching, the first best becomes attainable with a simple price-quantity contract. (JEL D86, K12)